PENGARUH KEPEMIMPINAN TERHADAP PENGAMBILAN KEPUTUSAN DENGAN STANDAR PELAYANAN MINIMAL DIKANTOR KELURAHAN TUALANG KECAMATAN PERBAUNGAN KABUPATEN SERDANG BEDAGAI - Intan Harefa; Prilmawati Zebua (Jurnal Genta Mulia, 2024)
The purpose of this research is to find out how much influence leardership has on decision making with minimum service standars in the Tualang Village Office, Perbaungan District, Serdang Bedagai Regency. The method used in this research is a quantilative method. To determine the significant level of influence of Lerdership on Decision Making with Minimum Service Standars in the Tualang Village Office, Perbaungan District, Serdang Bedagai Regency, a hypothesis test was carried out on r by determining the real level = 5%. Determine the r table test n = 33. It is known based on data processing that the result of the r table value using SPSS version 23.0, the result of X (leardership) t count 3.250 so in this case Z (SPM) t count 6.070 is greather than t table 2.0422 so there is a significant influence. And the regression analysis shown that variable X is 0.003. and variable Z is 0.000 and is smaller than 0.05. So that the Lerdership and minimum servive standars variables influence decision making.